PENGARUH WORK-LIFE BALANCE TERHADAP KINERJA DAN KEPUASAN KERJA KARYAWAN DI PERUSAHAAN MULTINASIONAL - Grace Maria Hutagaol; Intan Juwita; Nissa Nuralfi Azizah; Nita Sri Rahma; Sarinah Sihombing (Ensiklopedia of Journal, 2026)
The increasing complexity of global work systems has made work-life balance (WLB) a strategic concern in human resource management, particularly within multinational companies. This study aims to examine the influence of WLB on employee performance and job satisfaction through a comprehensive literature review approach. By synthesizing research published between 2021 and 2025, the study identifies key patterns and mediating relationships that link WLB with organizational outcomes. The analysis reveals that WLB positively affects job satisfaction by improving psychological well-being, reducing stress, and enhancing employee motivation. Furthermore, job satisfaction functions as a mediating variable that strengthens the relationship between WLB and performance, indicating that employees who achieve a balanced life tend to perform better and show greater commitment to their organizations. However, the effectiveness of WLB varies across organizations, depending on managerial support, cultural adaptability, and policy flexibility. This study contributes theoretically by consolidating recent empirical evidence on WLB within multinational contexts, and practically by emphasizing the need for HR policies that integrate flexible work arrangements, mental health support, and wellness-oriented reward systems.Keywords: work-life balance, job satisfaction, employee performance, multinational companies, human resource management.